Molecular characterization of methicillin-resistant Staphylococcus aureus clinical strains from the endotracheal tubes of patients with nosocomial pneumonia - Roberto Cabrera; Laia Fernández-Barat; Anna Motos; Rubén López-Aladid; Nil Vázquez; Mauro Panigada; Francisco Álvarez-Lerma; Yuly López; Laura Muñoz; Pedro Castro; Jordi Vila; Antoni Torres (Antimicrobial Resistance and Infection Control, 2020)
Abstract Background Among all cases of nosocomial pneumonia, Staphylococcus aureus is the second most prevalent pathogen (17.8%). In Europe, 29.9% of the isolates are oxacillin-resistant. The changing epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) nosocomial infections and the decreasing susceptibility to first-line antibiotics leave clinicians with few therapeutic options. The objective of our study was to determine the antimicrobial susceptibility, the associated molecular mechanisms of resistance and the epidemiological relatedness of MRSA strains isolated from the endotracheal tubes (ETT) of intubated critically ill patients in the intensive care unit (ICU) with nosocomial pneumonia caused by Staphylococcus aureus. Methods The antimicrobial susceptibility to vancomycin, linezolid, ciprofloxacin, clindamycin, erythromycin, chloramphenicol, fusidic acid, gentamicin, quinupristin-dalfopristin, rifampicin, sulfamethoxazole/trimethoprim, and tetracycline were measured. Resistance mechanisms were then analyzed by polymerase chain reaction and sequencing. Molecular epidemiology was carried out by multi-locus sequence typing. Results S. aureus isolates were resistant to ciprofloxacin, erythromycin, gentamicin, tetracycline, clindamycin, and fusidic acid. The most frequent mutations in quinolone-resistant S. aureus strains were S84L in the gyrA gene, V511A in the gyrB gene, S144P in the grlA gene, and K401R/E in the grlB gene. Strains resistant to erythromycin carried the ermC, ermA, and msrA genes; the same ermC and ermA genes were detected in strains resistant to clindamycin. The aac(6′)-aph(2″) gene was related to gentamicin resistance, while resistance to tetracycline was related to tetK (efflux pump). The fusB gene was detected in the strain resistant to fusidic acid. The most frequent sequence types were ST22, ST8, and ST217, which were distributed in four clonal complexes (CC5, CC22, CC45, and CC59). Conclusions High levels of resistance to second-line antimicrobials threatens the treatment of nosocomial respiratory infections due to methicillin-resistant S. aureus with decreased susceptibility to linezolid and vancomycin. The wide genotypic diversity found reinforces the central role of ICU infection control in preventing nosocomial transmission.